Escapism in Anita Desai’s Voices in the City: Exploring Inner Realities in Anita Desai's Fiction (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Anita Desai is undoubtedly one of the most powerful contemporary Indian novelists. A thorough study of the works of Anita Desai reveals that the main concern of her fiction is the exploration of human psyche. She believes in portrayal of inner reality. Anita Desai’s fiction art is different from that of other women novelist of India. Born of German mother and Bengali Father, She takes up characters from the upper middle class families in her fiction in a confident manner whether Nayan Tara Sehgal and Kamal Markandya concern themselves primarily with the external political and social circumstances of their characters, Desai concentrates in their inner life of her characters she herself said once that written for her meant “plugging into the depths of the mind of my characters”.